Predictive Factors for Drain Placement After Laparoscopic Cholecystectomy - Calini, Giacomo; Brollo, Pier Paolo; Quattrin, Rosanna; Bresadola, Vittorio (Frontiers in Surgery, 2022)
Purpose: Currently, surgical drainage during a laparoscopic cholecystectomy (LC) is still placed in selected patients. Evidence of the non-beneficial effect of the surgical drain comes from studies with a heterogeneous population. This preliminary study aims to identify any clinical, demographic, or intraoperative predictive factors for surgical drain placement during LC as first step to identify population for a prospective randomized study. Method: A case-control study was conducted in a single referral center and academic hospital between 2014 and 2018. Patients who underwent unconverted LC were divided into two groups: Group A (drain), Group B (no drain). We explored baseline, preoperative, intraoperative characteristics, and postoperative outcomes. Results: Between 409 patients who underwent LC: 90 (22%) patients were in Group A (drain). Age >64 years, male sex, cholecystitis, CCI ≥1, experienced surgeon, intraoperative technical difficulties, need of an additional trocar, operative time >60 min, and estimated blood loss >10 ml were predictive factors at univariate analysis. While at multivariate analysis, cholecystitis (OR:2,8, 95% CI:1,5-5,1; p<0,001), CCI ≥1 (OR:1,9, 95% CI:1,0-3,5; p=0,05), intraoperative technical difficulties (OR:3,6, 95% CI:1,8-6,2; p<0,001), need of an additional trocar (OR:2,5, 95% CI: 1,4-4,4; p<0,005), and estimated blood loss >10 ml (OR:3,0, 95% CI:1,7-5,3; p<0,0001) were predictive factors for surgical drain placement during LC. Conclusions: This study identified predictive factors that currently drive the surgeons to a surgical drain placement after laparoscopic cholecystectomy. Randomized prospective studies are needed to define the use of drain placement in these selected patients.